Reflection on the Role of Women in Banyumas Folklore: How Can It be Reconstructed in Gendered Literary Education? - Meina Febriani; Agus Nuryatin; Teguh Supriyanto; Hari Bakti Mardikantoro (International Conference on Science, Education, and Technology, 2023)
Banyumas folklore is a cultural heritage which contains the values, norms and understanding of the local community. However, the role of women in folklore is often trapped in gender stereotypes and subordination which limit their potential. Through the use of feminist theory and a critical approach, this article discusses the importance of criticizing the representation of women in Banyumas folklore and how literary education can be a medium to build awareness of gender equality. This article has two objectives: (1) to examine the role of women in Banyumas folklore and (2) how their representation can be reconstructed in literary education with gender perspective. A qualitative approach was carried out with the artifacts of the Banyumas folklore which becomes the important data in this study. This article has two important points. First, exploring the role of women in Banyumas folklore involving women characters and identifying their depictions. This role can be seen from a domestic and public perspective which has implications for the active and passive roles of women figures. Second, reconstructing the role of women in Banyumas folklore to make it more inclusive and promote gender equality. There are four reconstruction strategies: (1) strengthening the role of women characters, (2) changing the central point of perspective of women characters, (3) changing gender stereotypes in the substance of the story, and (4) using gender-inclusive language. In addition, this research also contributes to the construction of a gender perspective literary education strategy that can expand the role and contribution of women in Banyumas folklore.